2008
DOI: 10.1143/jjap.47.1429
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cell Survival and Yield of Rat Small Hepatocytes by Honeycomb-Patterned Films

Abstract: Surface designing of substrate to regulate cell adhesion and function in nano and micro scale is a critical issue in biomaterial science. In this study, we describe the fabrication of highly regular patterned porous films (honeycomb-patterned film) formed by a simply casting technique, and the culture of mature hepatocytes and small hepatocytes on the films. The pore size of the honeycomb-patterned films used was 6, 12, and 16 mm. We evaluated the effect of the honeycomb-patterned films on the morphology, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Thus, the growth time is decided by the evaporation time. Shimomura and Yan et al reported that the diameter of the pores in BFA was easy to regulate by the thickness of the cast polymer solution because the evaporation time varied with the thickness. For the same reason, the pores in the center of the BFA films are larger than those near the edge of the film because the thickness of the solution at the center of the drop is larger. , …”
Section: Formation Mechanism For Bfa Filmsmentioning
confidence: 99%
“…Thus, the growth time is decided by the evaporation time. Shimomura and Yan et al reported that the diameter of the pores in BFA was easy to regulate by the thickness of the cast polymer solution because the evaporation time varied with the thickness. For the same reason, the pores in the center of the BFA films are larger than those near the edge of the film because the thickness of the solution at the center of the drop is larger. , …”
Section: Formation Mechanism For Bfa Filmsmentioning
confidence: 99%
“…A similar value of albumin production in flat films and the honeycomb film was observed for small hepatocytes. 159 A commercially available block copolymer polystyrene-b-polybutadiene-b-polystyrene was used to obtain honeycomb membranes that were photochemically cross-linked by UV-light. The membranes did not show cytotoxicity and upon exposure to radiation, the surface hydrophobicity decreased, which allowed for cell attachment and proliferation of the lung cancer cell line A549.…”
Section: Substrates For Raman Spectroscopymentioning
confidence: 99%
“…This produces ordered patterns of hexagonally-packed holes in organic materials similar to the arrangement of cavities in the wax of a honeycomb, and has been extensively demonstrated by Shimomura and coworkers [78][79][80]. Formation of such patterns has been realized with many substances [81,82], some of which can be used as media for cell culture [83,84], as a superhydrohobic surface [85,86], or as a superadhesive surface [87].…”
Section: From Liquid Phase To Solid Interfacesmentioning
confidence: 93%